Forest fire risk zones delimited with the Normalized Differentiated Burning Radius (DNBR) in the Sierra Norte of Oaxaca, Mexico - Mario Ernesto Suárez-Mota; Teresa Elvira Martínez-Martínez; Faustino Ruiz-Aquino; César Valenzuela-Encinas; Rosalio Gabriel-Parra; Wenceslao Santiago-García (Botan‪ical Sciences)
Background: Forest fires play a crucial role in ecosystem dynamics, bringing both positive and negative effects that significantly impact areas like the Sierra Norte de Oaxaca (SNO).